The dopant type and amount governs the electrochemical performance of graphene platforms for the antioxidant activity quantification1. Issue 19 (21st May 2015) - Hui, Kai Hwee; Ambrosi, Adriano; Sofer, Zdeněk; Pumera, Martin; Bonanni, Alessandra
<x xml:space="preserve">Abstract</x> Graphene doped with heteroatoms can show new or improved properties as compared to the original undoped material. Boron-doped graphene and nitrogen-doped graphene containing different amounts of dopants were compared for the detection of gallic acid.